2004
DOI: 10.1007/s00216-004-2500-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of arsenic and antimony in naphtha by electrothermal atomic absorption spectrometry with microemulsion sample introduction and iridium permanent modifier

Abstract: This paper reports the determination of arsenic and antimony in naphtha by employing electrothermal atomic absorption spectrometry (ETAAS) as the analytical technique. In order to promote the direct determination of the analytes in the very volatile naphtha, the formation of a microemulsion with different surfactants (Triton X-100 and Brij-35) and different chemical modification strategies were tested. The results indicated that Triton X-100 is the best emulsification agent for naphtha in both As and Sb determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…For the analysis of a spiked SRM sample, only a Ru permanent modifier was used. Very similar data were obtained by Cassella et al [41], who compared Ir and WC+Ir permanent modifiers with a regular Pd(NO 3 ) 2 modifier for the determination of antimony in a naphtha emulsion. As application of the permanent Ir modifier enhanced the graphite tube lifetime twofold compared to that when a regular Pd modifier was used (150 cycles), the former modifier was finally chosen.…”
Section: Sbsupporting
confidence: 76%
See 2 more Smart Citations
“…For the analysis of a spiked SRM sample, only a Ru permanent modifier was used. Very similar data were obtained by Cassella et al [41], who compared Ir and WC+Ir permanent modifiers with a regular Pd(NO 3 ) 2 modifier for the determination of antimony in a naphtha emulsion. As application of the permanent Ir modifier enhanced the graphite tube lifetime twofold compared to that when a regular Pd modifier was used (150 cycles), the former modifier was finally chosen.…”
Section: Sbsupporting
confidence: 76%
“…It appears that there are some specific effects in the As-Rh-Na 2 SO 4 system leading to [ 41] suppression of peak area for arsenic in the presence of as few as 10 ng of sulfate ion [32]. In the presence of sodium sulfate and platinum modifier, a slight permanent decrease in the arsenic signal was noted in the region 600-1400 8C.…”
Section: Asmentioning
confidence: 93%
See 1 more Smart Citation
“…As can be seen in Figure 2, there is a significant difference between the analyzed standards. The sensitivities of the analytical curves for pure biodiesel (samples S 1 to S 7 ) are consistently lower for the aqueous standard, confirming the reports of some studies in the literature that the sensitivities of emulsified standards differ from those of aqueous standards (Cassella et al, 2004;Reyes  Campos, 2005;Saint´Pierre et al, 2002, 2003. It was also found that the analytical curves of the biodiesel samples did not exhibit the same sensitivity, although they were similar.…”
Section: Evaluation Of the Influence Of Standards In The Determinatiosupporting
confidence: 84%
“…These methods were described in several papers for the direct determination of trace elements in petroleum derivatives [5,[11][12][13]. Procedures to obtain one-phase microemulsions or conventional emulsions were also proposed for the determination of As [7,14,15].…”
Section: Introductionmentioning
confidence: 99%